Analisis Kebijakan Pengembangan Kompetensi Pegawai di Indonesia - Awang Anwaruddin (Jurnal Wacana Kinerja, 2020)
The issue on the need for developing the competency of Indonesia apparatus appeared when the government found difficulties to overcome the multi-dimension crisis by the dawn of the last century. To implement it, the government published Law Number 43/1999 as the change of Law apparatus competency as professional, neutral, clean from corruption, collution, and nepotism, and having a unity and nation perception. A year later, the government published the competencies needed for various positions in the government institution which are significant for formulating the curricula of competency based development programs-except the Standard of General Cometencies for Structural Officials published in 2001. Such ambiguity impacts on the ineffectivity of cometency development process in Indonesia.